Mental wellbeing and social resilience of eritrean refugees living in Germany - Gebresilassie, Temesghen; Beiersmann, Claudia; Ziegler, Sandra; Keck, Verena; Kidane, Yonas Semere; Jahn, Albrecht; Benson-Martin, Janine (International journal of environmental research and public health, 2022)
Mental health and social resilience play a significant role in refugees’ adaptation during the resettlement process in the host country. Maintaining good mental wellbeing helps the refugees to respond to stressful experiences with healthy life choices. This study aimed to explore the mental wellbeing and social resilience of Eritrean refugees living in Germany and to identify social conditions and enablers to foster adaptation. This study employs a qualitative approach with a semi-structured, in-depth interview data collection method. Informants were identified among mostly young adult refugees living in Heidelberg, Germany, with a migration history of 3-6 years. In total, 15 informants were recruited through snowball sampling. Data were sorted and analyzed using the five pillars of the Adaptation and Development after Persecution and Trauma (ADAPT) model. The findings suggest that Eritrean refugees experienced psychological distress after resettlement in Germany; however, with time, their mental health improved. The study revealed conditions that were experienced as hindrances, as well as ones that were considered to be resources of positive mental wellbeing and social resilience for resettled refugees. Resettlement challenges described by the participants were the language barrier, discrimination, unemployment, insecure residence status, loss of family and friends, conflict within the diaspora community, and isolation. The main sources of mental wellbeing and social resilience include the feeling of being welcomed by local communities, access to social services, adopting new relationships, and educational opportunities. These experiences encouraged refugees to have a favorable view of their lives and futures and were also found to facilitate better integration and adaptation. Understanding refugee mental wellbeing and social resilience requires a multidimensional perspective. Eritrean refugees living in Germany have experienced and are still experiencing resettlement challenges, such as, for example, loss of family and friends, negative perception of the German system, loss of past achievements, or unemployment. However, they have developed adaptive and resilience mechanisms, as well, such as seeing an opportunity for a better life, adopting new roles, and accepting Germany as a “second home”. In addressing those issues reported by the refugees as hindrances, these could be turned into sources of mental wellbeing and resilience.